The Concept of Islamic Education: A Comparative Study of Ibn Katsir's and Al-Misbah's Tafsir of QS. Al-Anbiya’: 7: Konsep Pendidikan Islam: Studi Komparasi Tafsir Ibnu Katsir dan Tafsir Al-Misbah pada QS. Al-Anbiya’ (21): 7 - Khofifah; Eko Prayetno (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2024)
There are many studies on Islamic education from the perspective of the Qur'an. But few studies of Islamic education according to QS. Al-Anbiya': 7 from the perspective of classical and contemporary scholars. This study aims to determine the model, method, and style of Ibn Katsir’s and Al-Misbah's interpretation as well as the value of Islamic education in QS. Al-Anbiya': 7. This research design uses a literature review. Primary sources are the Ibn Katsir and Al-Misbah interpretations. Secondary sources are articles and literature related to the concept of Islamic education from the perspective of Qur'anic interpretation. Then researchers compare the concept of Islamic education in QS. Al-Anbiya': 7 according to Ibn Katsir’s and Al-Misbah's interpretation. The results showed that the model of Ibn Katsir interpretation is classical because it uses the form of tafsir bil ma'tsur, the method used is the tahlili method, the style of interpetation uses tartib mushafi, and sometimes it uses ratios / reasoning. While Al-Misbah's interpretation model is contemporary because it uses the form of tafsir bi al-ra'yi and the method used is tahlili, the style of interpretation tends to use the literary style of social culture. The value of Islamic education in QS. Al-Anbiya': 7 that can be applied today is the importance of asking people who are knowledgeable about lifelong learning in order to become broad-minded and knowledgeable people so that it can lead us to a good and right path according to the teachings of Islam. Aabstrak Ada banyak penelitian tentang pendidikan Islam dalam perspektif al-Qur’an. Namun, masih sedikit kajian pendidikan Islam menurut QS. Al-Anbiya’: 7 perspektif ulama klasik dan kontemporer. Penelitian ini bertujuan untuk mengetahui bentuk, metode, dan corak tafsir Ibnu Katsir dan tafsir Al-Misbah serta konsep nilai pendidikan Islam pada QS. Al-Anbiya’: 7. Desain penelitian ini menggunakan tinjauan pustaka. Sumber primer adalah Tafsir Ibnu Katsir dan Tafsir Al-Misbah dan sumber sekunder berupa artikel dan literatur yang berkaitan dengan konsep pendidikan Islam dari sudut pandang penafsiran Al-Qur'an. Kemudian peneliti bandingkan konsep pendidikan Islam dalam QS. Al-Anbiya’: 7 menurut tafsir Ibnu Katsir dan tafsir Al-Misbah. Hasil penelitian menunjukkan bahwa model Tafsir Ibnu Katsir adalah klasik karena menggunakan bentuk tafsir bil ma’tsur, metode yang digunakan yaitu metode tahlili, corak tafsir menggunakan tartib mushafi, dan terkadang menggunakan rasio/penalaran. Sedangkan model tafsir Al-Misbah adalah kontemporer, karena menggunakan bentuk tafsir bi al-ra’yi, metode yang digunakan yaitu tahlili, corak tafsir cenderung menggunkan corak sastra budaya kemasyarakatan. Nilai pendidikan Islam dalam QS. Al-Anbiya’: 7 yang dapat diterapkan pada zaman sekarang adalah pentingnya bertanya kepada orang yang berilmu (berguru) dan belajar sepanjang hayat agar menjadi pribadi yang luas wawasan dan berilmu sehingga dapat menuntun kita ke jalan yang baik dan benar sesuai ajaran agama Islam.